Do high‐dose corticosteroids improve outcomes in hospitalized COVID‐19 patients?. Issue 1 (8th October 2021) - Kumar, Gagan; Patel, Dhaval; Hererra, Martin; Jefferies, David; Sakhuja, Ankit; Meersman, Mark; Dalton, Drew; Nanchal, Rahul; Guddati, Achuta Kumar
Abstract: Coronavirus disease 2019 (COVID‐19) is characterized by dysregulated hyperimmune response and steroids have been shown to decrease mortality. However, whether higher dosing of steroids results in better outcomes has been debated. This was a retrospective observation of COVID‐19 admissions between March 1, 2020, and March 10, 2021. Adult patients (≥18 years) who received more than 10 mg daily methylprednisolone equivalent dosing (MED) within the first 14 days were included. We excluded patients who were discharged or died within 7 days of admission. We compared the standard dose of steroids (<40 mg MED) versus the high dose of steroids (>40 mg MED). Inverse probability weighted regression adjustment (IPWRA) was used to examine whether higher dose steroids resulted in improved outcomes. The outcomes studied were in‐hospital mortality, rate of acute kidney injury (AKI) requiring hemodialysis, invasive mechanical ventilation (IMV), hospital‐associated infections (HAI), and readmissions. Of the 1379 patients meeting study criteria, 506 received less than 40 mg of MED (median dose 30 mg MED) and 873 received more than or equal to 40 mg of MED (median dose 78 mg MED). Unadjusted in‐hospital mortality was higher in patients who received high‐dose corticosteroids (40.7% vs. 18.6%, p < 0.001). On IPWRA, the use of high‐dose corticosteroids was associated with higher odds of death (odds ratio [OR] 2.14; 95% confidence interval [CI] 1.45–3.14, p < 0.001) but not with the development of HAI, readmissions, or requirement of IMV. High‐dose corticosteroids were associated with lower rates of AKI requiring hemodialysis (OR 0.33; 95% CI 0.18–0.63). In COVID‐19, corticosteroids more than or equal to 40 mg MED were associated with higher in‐hospital mortality. Highlights: In this observational study of 1379 patients, using Inverse probability weighted regression adjustment, those receiving 30 mg (IQR 24‐34 mg) methylprednisolone equivalent dose (MED) had lower in hospital mortality than those with 78 mg (IQR 59‐108 mg) MED. Higher dose steroids were not associated with better improvements in inflammatory markers, rates or duration of mechanical ventilation or readmissions. Higher dose steroids were however, associated with lower rates of acute kidney injury requiring hemodialysis. Dosage higher than 80 mg MED were associated with higher rates of hospital acquired infections.